Relationship marketing in the digital age - Palmatier, Robert W.; Steinhoff, Lena (New York : Routledge, 2019)
The concept of relationship marketing has been discussed among marketing academics and managers since the early 1980s. But instead of reaching its maturity stage, relationship marketing is nowadays encountering its next upsurge. Due to a confluence of trends driving the global business world--including the transition to service-based economies, faster product commoditization, intensified competition worldwide, growth among emerging markets, aging populations, advertising saturation, and (above all) the digital age--strong customer relationships are more than ever vital to company strategy and performance. Relationship Marketing in the Digital Age provides a comprehensive overview of the state-of-the-art of relationship marketing, offering fruitful insights to marketing scholars and practitioners. In seven chapters, divided into two main sections on understanding (Part I) and effectively applying (Part II) relationship marketing, an introductory and a concluding chapter, readers learn how to successfully manage customer-seller relationships.
Introductory chapter -- Relationship marketing and the digital age -- Understanding relationship marketing -- Relationship marketing theory -- Relationship marketing framework -- Applying relationship marketing -- Relationship marketing dynamics -- Relationship marketing strategies -- Relationship marketing targeting -- Research and managerial guidelines for relationship marketing in the digital age -- References -- Glossary -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Relationship marketing; Marketing -- Technological innovations; Customer relations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Consumer Behavior